Analisis Sentimen Pengguna Aplikasi Gopay di X Menggunakan Algoritma Naïve Bayes Classifier (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze GoPay user sentiments on the X social media platform (formerly known as Twitter) using the Naive Bayes Classifier algorithm. Sentiment analysis was conducted to understand user perceptions and satisfaction levels towards GoPay digital payment services based on their shared comments and reviews. Data was collected through a tweet crawling process containing the keyword